Ex Aequo et Bono as a Manifestation of Legal Justice for Society - Huda, Arsha Nurul (Damhil Law Journal, 2021)
One of the principles that can be taken by judges as part of the implementation of the freedom of judges in the enforcement of the verdict is by the way of applying the principle et aequo et bono. The application of the principle of ex aequo et bono still invites a lot of debate. Furthermore, the existence of the principle ex aequo et bono is sometimes considered Contrary to the arrangement of the ultra petita principle.This research aims to identify the existence of the principle of ex aequo et bono in civil event law in Indonesia and analyze its application practices to find out how the implications of applying the principle in the fulfillment of justice for society. The research was conducted by approaching the legislation and consideration of judges using primary legal materials in the form of Law No. 48 of 2009 on Judicial Power and secondary legal materials in the form of written works relevant to the application of the principle of ex aequo et bono to be analyzed comprehensively.The results showed that the application of the principle of ex aequo et bono is basically a juridical act that has a legal basis and the Judge remains bound by the terms of speech. The application of the principle of ex aequo et bono provides an opportunity for judges to perform ex officio actions based on the view of justice so that the judge's decision serves as a counterweight that is not only limited to deciding the case, but also resolving the problems that have been filed.